2019
DOI: 10.6001/actamedica.v26i1.3952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane and desflurane on early cognitive changes after thyroid surgery: interim results

Abstract: Background. These are primary results of a randomized double-blinded study comparing postoperative changes in cognitive functions and the effect of desflurane and sevoflurane on these changes.Materials and methods. The study includes patients of ≥40 years of age undergoing elective thyroid surgery under general anaesthesia. Patients were randomly allocated to either sevoflurane or desflurane group. Cognitive testing (memory, attention, and reasoning tasks) was performed a day before surgery and repeated 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Sevoflurane is mostly used for intraoperative anesthesia, and although the surgical procedure ITSELF may impact neuroinflammation, sevoflurane can exacerbate this neural damage. Sevoflurane can induce and exacerbate neuroinflammation by stimulating the production of inflammatory factors such as IL‐1β and TNF‐α; it can also induce neuronal oxidative damage by activating calcium‐dependent proteases, leading to the generation of a large number of oxygen free radicals, which promotes neuronal apoptosis and results in cognitive dysfunction 14–16 . TEMPOL is a novel free radical scavenger with the advantages of high stability and low molecular weight and has been widely used in research regarding ischemia‐reperfusion in the kidney, liver, and spinal cord 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sevoflurane is mostly used for intraoperative anesthesia, and although the surgical procedure ITSELF may impact neuroinflammation, sevoflurane can exacerbate this neural damage. Sevoflurane can induce and exacerbate neuroinflammation by stimulating the production of inflammatory factors such as IL‐1β and TNF‐α; it can also induce neuronal oxidative damage by activating calcium‐dependent proteases, leading to the generation of a large number of oxygen free radicals, which promotes neuronal apoptosis and results in cognitive dysfunction 14–16 . TEMPOL is a novel free radical scavenger with the advantages of high stability and low molecular weight and has been widely used in research regarding ischemia‐reperfusion in the kidney, liver, and spinal cord 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane can induce and exacerbate neuroinflammation by stimulating the production of inflammatory factors such as IL‐1β and TNF‐α; it can also induce neuronal oxidative damage by activating calcium‐dependent proteases, leading to the generation of a large number of oxygen free radicals, which promotes neuronal apoptosis and results in cognitive dysfunction. 14 , 15 , 16 TEMPOL is a novel free radical scavenger with the advantages of high stability and low molecular weight and has been widely used in research regarding ischemia‐reperfusion in the kidney, liver, and spinal cord. 17 Qi et al 18 found via in vitro experiments of Takotsubo syndrome that TEMPOL could improve oxidative dysfunction of mitochondria through the reactive oxygen/mitochondrial/antiapoptotic/p38 MAPK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have investigated the impact of anesthetic agents on recovery and postoperative cognition, but it is difficult to compare our findings to theirs, since most of them were performed in elderly patient populations and have different methodologies, mainly using the Mini-Mental State Examination (MMSE) [5][6][7][8][9][10][11][12][13][14]. Additionally, they mostly focus on postoperative delirium in older age groups and postoperative cognitive dysfunction (POCD) that appears after patient discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, those which focused on recovery characteristics, suggest that desflurane is superior [6,8,13] or comparable to sevoflurane [10,11]. Similarly, studies focused on cognitive function, find desflurane slightly superior [7,8,12] or equivalent to sevoflurane [5,9,10,14]. To our knowledge there are no studies investigating early recovery and cognitive characteristics in younger patients with DS or any intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation